Witchcraft, Justice, and Human Rights in Africa: Cases from Malawi. (16th March 2015) - Ashforth, Adam
Abstract: The human rights approach to witchcraft accusations denies their validity and forecloses the possibility of a trial, fair or otherwise. While there is much to be said for a bracing rationalism in all aspects of life, evidence from Africa over the past couple of centuries shows no sign that witchcraft narratives lose their plausibility as a result of people being told that witches do not exist. Résumé: L'exclusion des accusations de sorcellerie dans le contexte de la gestion des droits de l'homme annule leur réalité et exclut la possibilité de rendre justice en cas d'accusation infondée. Bien qu'il y ait beaucoup à dire pour soutenir un rationalisme solide dans tous les aspects de la vie, des études de cas menées au cours des deux derniers siècles en Afrique démontrent que les récits de sorcellerie n'ont rien perdu de leur crédibilité en dépit des discours publics niant l'existence des sorcières.